Efficacy, Safety, and Potential Biomarkers of Sunitinib and Transarterial Chemoembolization (TACE) Combination in Advanced Hepatocellular Carcinoma (HCC): Phase II Trial. (April 2018) - Pokuri, Venkata K.; Tomaszewski, Garin M.; Ait-Oudhia, Sihem; Groman, Adrienne; Khushalani, Nikhil I.; Lugade, Amit A.; Thanavala, Yasmin; Ashton, Edward A.; Grande, Catherine; Fetterly, Gerald J.; Iyer, Renuka
Abstract : Objectives: To evaluate the safety/efficacy and explore biomarkers for a rationally designed combination of sunitinib and transarterial chemoembolization (TACE) in a prospective phase 2 study of advanced hepatocellular carcinoma (HCC). Methods: Inoperable HCC patients with Child-Pugh A disease received 37.5 mg sunitinib from days 1 to 7 followed by TACE on day 8. Sunitinib was resumed from days 15 to 36 followed by 2 weeks off. Patients received subsequent sunitinib cycles of 4 weeks on and 2 weeks off. Dynamic contrast-enhanced magnetic resonance imaging and circulating soluble biomarkers were assessed at baseline, day 8, day 10, and day 36. Results: Sixteen patients with liver only (n=10) and extrahepatic disease (n=6) were enrolled. After a median follow-up of 12.8 months, 2 partial responses, 11 stable disease, and 3 clinical deteriorations were seen for a clinical benefit rate of 81%. Median progression-free survival (PFS) was 8 months (95% CI, 4.3-9.3) and overall survival was 14.9 months (95% CI, 6.3-27.1). Eleven of 16 patients (69%) had grade 3/4 toxicities attributable to sunitinib, the most frequent being thrombocytopenia, amylase/lipase elevations, lymphopenia, and fatigue. Mean K trans (volume transfer constant) and viable tumor percent in consented patients decreased by 27% and 14.8%, respectively, with combination therapy. Soluble vascular endothelial growth factor receptor-2 (sVEGFR2) levels, cytokines (interleukin-8, interleukin-21), and monocytes decreased with combination therapy. Estimated sunitinib IC50 values of 15 and 10 ng/mL modulated K trans and AUC90. sVEGFR2 levels decreased with K trans and AUC90. Conclusions: Encouraging progression-free survival and overall survival were seen with acceptable toxicity in our study of sunitinib and TACE combination in advanced HCC. Potential imaging and serum biomarkers showed increased benefit with combination therapy. Abstract : Supplemental Digital Content is available in the text.